Directions of comparative linguacultural studies - Oyxunboyeva Dilafròz Mahmud qizi; Niyatova Maftuna Norbek qizi ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2023)
This article deals with the analysis of comparative linguacultural studies and the directions of linguacultual studies